2005
DOI: 10.1038/sj.gt.3302603
|View full text |Cite
|
Sign up to set email alerts
|

An adenovirus vector with a chimeric fiber incorporating stabilized single chain antibody achieves targeted gene delivery

Abstract: Adenovirus (Ad) vectors are of utility for many therapeutic applications. Strategies have been developed to alter adenoviral tropism to achieve a cell-specific gene delivery capacity employing fiber modifications allowing genetic incorporation of targeting motifs. In this regard, single chain antibodies (scFv) represent potentially useful agents to achieve targeted gene transfer. However, the distinct biosynthetic pathways that scFv and Ad capsid proteins are normally routed through have thus far been problema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
54
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(54 citation statements)
references
References 42 publications
0
54
0
Order By: Relevance
“…Vector attachment to FRa was redirected, but gene delivery was not achieved (47). Display of scFvs on adenoviruses remains challenging as the folding of scFv occurs in the endoplasmic reticulum, whereas adenoviral assembly does not (48,49).…”
Section: Discussionmentioning
confidence: 99%
“…Vector attachment to FRa was redirected, but gene delivery was not achieved (47). Display of scFvs on adenoviruses remains challenging as the folding of scFv occurs in the endoplasmic reticulum, whereas adenoviral assembly does not (48,49).…”
Section: Discussionmentioning
confidence: 99%
“…117 On this basis, rational development of complex ligands with cytoplasmic solubility and stability will be required for their application to Ad vectors. Exemplifying this concept, Hedley et al 118 have developed a singlecomponent antibody-targeted Ad vector by incorporating a novel, cytoplasmically stable scFv into a de-knobbed fiber. This vector demonstrated selective targeting to its cognate epitope expressed on the membrane surface of cells, and suggests that cytoplasmic stability of the targeting molecule, per se, allows retention of antigen recognition in the Ad capsid-incorporated context.…”
Section: Adenovirus Targeting Via Genetic Modification: Fibermentioning
confidence: 99%
“…The stock virus was then used to infect HEK293 cells for the preparation of fiber-modified Ad. The viruses were purified on CsCl and dialyzed against Tris-buffered saline (20 mM Tris-HCl, pH 8.1) as previously described (19). The titers of the purified viruses were determined by measuring protein content using bovine serum albumin as a standard.…”
Section: Construction Of 9r Fste-modified Adenoviral Vectorsmentioning
confidence: 99%
“…It was found that the fiber knob at the C terminus, but not the N-terminal half (1 to 260 aa), was required for fiber trimer formation (23) since fiber proteins containing the knob and two or more shaft repeats form functional trimers. Those find-ings have since been used to guide fiber modification for improved gene delivery, including peptide insertion at the knob region or peptide fusion at the fiber C terminus (11,19,21,27,28,35). In most cases, the modified viruses retain the native tropism while regaining some specificity associated with the inserted oligopeptides.…”
mentioning
confidence: 99%
See 1 more Smart Citation